Functional nicotinic acetylcholine receptor reconstitution in Au(111)-supported Thiolipid Monolayers - Pissinis, Diego Ezequiel (2015)
The insertion and function of the muscle-type nicotinic acetylcholine receptor (nAChR) in Au(111)- supported thiolipid self-assembled monolayers have been studied by atomic force microscopy (AFM), surface plasmon resonance (SPR), and electrochemical techniques. It was possible for the first time to resolve the supramolecular arrangement of the protein spontaneously inserted in a thiolipid monolayer in an aqueous solution. Geometric supramolecular arrays of nAChRs were observed, most commonly in a triangular form compatible with three nAChR dimers of ∼20 nm each. Addition of the full agonist carbamoylcholine activated and opened the nAChR ion channel, as revealed by the increase in capacitance relative to that of the nAChR?thiolipid system under basal conditions. Thus, the self-assembled system appears to be a viable biomimetic model to measure ionic conductance mediated by ion-gated ion channels under different experimental conditions, with potential applications in biotechnology and pharmacology